Martin Luther King, Jr. - Ling, Peter J. (Peter John), 1956-, author.
1 online resource (viii, 382 pages)
Keywords: "Peter Ling's biography of Martin Luther King, Jr examines the man and the Civil Rights Movement, showing how King grew into his leadership role and kept his faith as the challenges facing the movement strengthened after 1965. Ling combines narrative of Martin Luther King's life with historiographical debates surrounding him and places both within the historical context of the Civil Rights Movement. This second edition includes an extended look at Black Power and a detailed analysis of the memorialization of King since his death, including President Obama's 50th anniversary address, and how conservative spokesmen have tried to appropriate King as an advocate of colour-blindness"--